Analisis Faktor Yang Mempengaruhi Masyarakat Muslim Menggunakan Jasa "Bank Emok" Di Desa Cilalawi Kecamatan Sukatani Kabupaten Purwakarta - Lisa Dewi Anggraeni; Moch. Cahyo Sucipto; Siti Rohmat (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2020)
The people of Cilalawi Village, Sukatani Subdistrict, Purwakarta Regency, have been making use of Bank Emok's loans only to meet consumer needs, because with their jobs whose income is uncertain they cannot meet their needs or needs quickly. With debt they can fulfill this and repay debt from their work. But not a few people also take advantage of debt for productive things, namely to make venture capital. The purpose of this study was to determine the enthusiasm of the Muslim community in Cilalawi Village Cilalawi Village Sukatani District Purwakarta Regency on the existence of "Emok Bank". To find out what factors influence the Muslim community in Cilalawi Village, Sukatani District, Purwakarta Regency, use the services of "Bank Emok". The research method used in this study is through a qualitative approach, where the qualitative approach is also called the naturalistic approach. Qualitative called because the nature of the data collected is qualitative, not quantitative, because it does not use measuring devices. While it is called naturalistic because the research field situation is natural or natural, as it is, without being manipulated, and without being regulated by experiments or tests. Naturalistic research looks at real situations that change naturally, are open, there is no engineering of controlling variables. Data collection techniques used in this study consisted of documentation, interviews. The results showed that the enthusiasm of the public in using the services of Emok Bank was quite large. On average in one Bank Emok has a number of customers of more than ten people there are even up to 40 people. Public enthusiasm can also be seen from the number of borrowed Emok Banks. Most people borrow more than one Emok Bank and even up to four Emok Banks at the same time. Cilalawi Village community uses the services of the Emok Bank influenced by internal factors that include the person such as age, economic situation, work, lifestyle and psychological factors such as motivation, perception and attitude of the community. External factors that influence the people of Desa Cilalawi in using the services of Emok Bank are cultural, social, and marketing.